2015
DOI: 10.1097/mcg.0000000000000212
|View full text |Cite
|
Sign up to set email alerts
|

Survival Benefit of Neoadjuvant Chemotherapy for Resectable Cancer of the Gastric and Gastroesophageal Junction

Abstract: There is convincing evidence for a survival benefit of NAT over surgery alone in patient with cancer of the gastric and gastroesophageal junction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 54 publications
(81 reference statements)
1
27
0
Order By: Relevance
“…Gastric cancer is an aggressive malignancy in which most patients treated with surgical resection develop disease recurrence, with a recent meta-analysis showing that 5-year survival for patients undergoing surgery is 42% if given neoadjuvant therapy and only 30% if not. 13 The present study indicates that presence of LI, VI and/or PNI is associated with poorer survival in patients with gastric adenocarcinoma who are treated with neoadjuvant therapy followed by gastrectomy with D2 lymphadenectomy, with PNI having prognostic significance independent of lymph node status. The reported prevalence of LI, VI and PNI is widely distributed, with PNI being reported between 2% and 48%, VI 7-44% and LI 10-91%.…”
Section: Discussionsupporting
confidence: 49%
“…Gastric cancer is an aggressive malignancy in which most patients treated with surgical resection develop disease recurrence, with a recent meta-analysis showing that 5-year survival for patients undergoing surgery is 42% if given neoadjuvant therapy and only 30% if not. 13 The present study indicates that presence of LI, VI and/or PNI is associated with poorer survival in patients with gastric adenocarcinoma who are treated with neoadjuvant therapy followed by gastrectomy with D2 lymphadenectomy, with PNI having prognostic significance independent of lymph node status. The reported prevalence of LI, VI and PNI is widely distributed, with PNI being reported between 2% and 48%, VI 7-44% and LI 10-91%.…”
Section: Discussionsupporting
confidence: 49%
“…There were 14 early stage cancers in the no NACT group, but patients in this group were older and had more comorbidity as well. A recent meta-analysis has suggested that neoadjuvant chemotherapy improves survival in patients with gastric and gastro-oesophageal junctional cancers [ 19 ]. Given that all patients are not eligible for NACT, these results are not applicable to all patients.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of treatment ranged from one day to three months and the mean age of trial participants was 60.2 years and range from 34 to 75 years. For the primary outcome of interest, six unique comparisons were available for 178,17,18,[32][33][34][35][36][37][38][39][40][41][42][43][44][45] different trials (one trial included two different comparisons). In terms of adverse effects, there were 158, 17-19, 32, 33, 35, 38-42, 46 trials providing data for seven unique comparisons.…”
mentioning
confidence: 99%